Belgian National Burden of Disease Study. Guidelines for the calculation of Disability-Adjusted Life Years in Belgium, June 2025 - Robby De Pauw; Rani Claerman; Vanessa Gorasso; Sarah Nayani; Aline Scohy; Laura Van den Borre; Jozefien Wellekens; Brecht Devleesschauwer (Sciensano, 2025)
Keywords: BeBOD; burden of disease; Burden of disease methodology; DALYs

Informal caregiving and mental health: results from the Belgian health interview survey 2013 and 2018 - Filip Van Droogenbroeck; Bram Spruyt; Pierre Gérain; Laura Van den Borre; Pierre Smith; Robby De Pauw; Sarah Dury (BMC Public Health, 2025)
Background Due to a globally ageing population, the demand for informal caregivers is increasing. This study investigates the socio-demographic profile of informal caregivers in Belgium and assesses the relationship between informal care (intensity and care recipients) and mental health, considering potential moderators like education, age, and gender. Methods Using population-based data from the 2013 and 2018 waves of the Belgian Health Interview Survey (N = 14,661), we conducted multivariate (multinomial/ordinal) logistic and linear regression analyses to examine the socio-demographic profile of informal caregivers and their psychological distress, measured through the General Health Questionnaire (GHQ-12). Results The prevalence of informal caregiving increased from 10.0% in 2013 to 13.0% in 2018. Informal caregivers were predominantly female, middle-aged, and often had no paid job. High-intensity caregivers (over 20 h/week) experienced significantly higher psychological distress compared to non-caregivers, whereas lower-intensity caregivers did not. Additionally, while gender, age, and education were significant predictors of who becomes a caregiver, they did not moderate the relationship between caregiving and mental health. Conclusions Our findings suggest that the stress of caregiving is more directly related to the nature and intensity of the caregiving tasks themselves rather than the demographic characteristics of the caregivers. Interventions aimed at reducing the adverse effects of caregiving might need to be universally applicable to all caregivers, focusing on reducing the intrinsic burdens of caregiving tasks rather than targeting demographic subgroups.
Keywords: GHQ-12; informal care; population study; PSYCHOLOGICAL DISTRESS; public health

Anxiety and depression in people with post-COVID condition: a Belgian population-based cohort study three months after SARS-CoV-2 infection - Stéphanie D’Hondt; Lydia Gisle; Robby De Pauw; Dieter Van Cauteren; Stefaan Demarest; Sabine Drieskens; Laura Cornelissen; Karin De Ridder; Rana Charafeddine; Pierre Smith (Social Psychiatry and Psychiatric Epidemiology, 2024)
Purpose: Since the onset of the COVID-19 pandemic, most research has focused on the management of the acute symptoms of the disease. Yet some people tend to experience symptoms beyond the acute phase, defined as Post-COVID-19 Condition (PCC). This study aims to assess the impact of COVID-19 and PCC on anxiety and depression. Methods: This is a prospective longitudinal cohort study among the Belgian adult population with recent SARS-CoV-2 infection for which contact tracing was initiated. A total of 3127 people were followed-up just after their infection and three months later (from April 2021 to January 2022). Anxiety and depression were assessed at the two stages using the GAD-7 (Generalized Anxiety Disorder) and the PHQ-9 (Patient Health Questionnaire). Results: Three months after infection, participants with PCC (50%) had an increased probability of having both anxiety and depressive symptoms (p < 0.001). The proportion with anxiety and depressive symptoms at three months were significantly higher in people with PCC (11% and 19%) compared to people without persistent COVID symptoms (3.8% and 4.2%) and to a matched sub-sample not infected with SARS-CoV-2 (6.5% and 4.3%). Having at least one acute COVID-19 symptom (p < 0.001), experiencing financial loss following the infection (p < 0.001), and different PCC symptoms were associated with anxiety and depressive symptoms worsening over time. Conclusions: This study showed that three months after a SARS-CoV-2 infection, one in two people suffer from PCC with significant consequences for their mental health. Follow-up on mental health must therefore have an important place in people suffering from PCC.
Keywords: Anxiety; COVID-19; dépression; Mental health; Post COVID-19 condition

Anxiety and depression in people with post-COVID condition: a Belgian population-based cohort study three months after SARS-CoV-2 infection. - Stéphanie D'Hondt; Lydia Gisle; Robby De Pauw; Dieter Van Cauteren; Stefaan Demarest; Sabine Drieskens; Laura Cornelissen; Karin De Ridder; Rana Charafeddine; Pierre Smith (Soc Psychiatry Psychiatr Epidemiol, 2024)
PURPOSE: Since the onset of the COVID-19 pandemic, most research has focused on the management of the acute symptoms of the disease. Yet some people tend to experience symptoms beyond the acute phase, defined as Post-COVID-19 Condition (PCC). This study aims to assess the impact of COVID-19 and PCC on anxiety and depression. METHODS: This is a prospective longitudinal cohort study among the Belgian adult population with recent SARS-CoV-2 infection for which contact tracing was initiated. A total of 3127 people were followed-up just after their infection and three months later (from April 2021 to January 2022). Anxiety and depression were assessed at the two stages using the GAD-7 (Generalized Anxiety Disorder) and the PHQ-9 (Patient Health Questionnaire). RESULTS: Three months after infection, participants with PCC (50%) had an increased probability of having both anxiety and depressive symptoms (p < 0.001). The proportion with anxiety and depressive symptoms at three months were significantly higher in people with PCC (11% and 19%) compared to people without persistent COVID symptoms (3.8% and 4.2%) and to a matched sub-sample not infected with SARS-CoV-2 (6.5% and 4.3%). Having at least one acute COVID-19 symptom (p < 0.001), experiencing financial loss following the infection (p < 0.001), and different PCC symptoms were associated with anxiety and depressive symptoms worsening over time. CONCLUSIONS: This study showed that three months after a SARS-CoV-2 infection, one in two people suffer from PCC with significant consequences for their mental health. Follow-up on mental health must therefore have an important place in people suffering from PCC.
Keywords: Adult; Aged; Anxiety; Anxiety Disorders; Belgium; Cohort Studies; COVID-19; dépression; Female; Humans; Longitudinal Studies; Male; middle aged; Post-Acute COVID-19 Syndrome; Prospective Studies; SARS-CoV-2

Anxiety and depression in people with post-COVID condition: a Belgian population-based cohort study three months after SARS-CoV-2 infection - Stéphanie D’Hondt; Lydia Gisle; Robby De Pauw; Dieter Van Cauteren; Stefaan Demarest; Sabine Drieskens; Laura Cornelissen; Karin De Ridder; Rana Charafeddine; Pierre Smith (Social Psychiatry and Psychiatric Epidemiology, 2024)
Purpose Since the onset of the COVID-19 pandemic, most research has focused on the management of the acute symptoms of the disease. Yet some people tend to experience symptoms beyond the acute phase, defined as Post-COVID-19 Condition (PCC). This study aims to assess the impact of COVID-19 and PCC on anxiety and depression. Methods This is a prospective longitudinal cohort study among the Belgian adult population with recent SARS-CoV-2 infection for which contact tracing was initiated. A total of 3127 people were followed-up just after their infection and three months later (from April 2021 to January 2022). Anxiety and depression were assessed at the two stages using the GAD-7 (Generalized Anxiety Disorder) and the PHQ-9 (Patient Health Questionnaire). Results Three months after infection, participants with PCC (50%) had an increased probability of having both anxiety and depressive symptoms (p < 0.001). The proportion with anxiety and depressive symptoms at three months were significantly higher in people with PCC (11% and 19%) compared to people without persistent COVID symptoms (3.8% and 4.2%) and to a matched sub-sample not infected with SARS-CoV-2 (6.5% and 4.3%). Having at least one acute COVID-19 symptom (p < 0.001), experiencing financial loss following the infection (p < 0.001), and different PCC symptoms were associated with anxiety and depressive symptoms worsening over time. Conclusions This study showed that three months after a SARS-CoV-2 infection, one in two people suffer from PCC with significant consequences for their mental health. Follow-up on mental health must therefore have an important place in people suffering from PCC.
Keywords: COVID-19; Mental health; post-COVID-19 condition

Assessing mental health from registry data: What is the best proxy? - Simon Beerten; Robby De Pauw; Van Pottelbergh, Gijs; Casas, Lidia; Vaes, Bert (International Journal of Medical Informatics, 2024)
Objective Medical registries frequently underestimate the prevalence of health problems compared with surveys. This study aimed to determine the registry variables that can serve as a proxy for variables studied in a mental health survey. Materials and methods Prevalences of depressive symptoms, anxiety and psychoactive medication use from the 2018 Belgian Health Interview Survey (HIS) were compared with same-year prevalences from INTEGO, a Belgian primary care registry. Participants aged 15 and above were included. We assessed correlation using Spearman’s rho (SR), and agreement using the intraclass correlation coefficient (ICC). We also calculated the limits of agreement (LOAs) for each comparison. HIS questions about depressive symptoms, anxiety and psychoactive medication use were compared with the following variables from INTEGO: symptom codes, diagnosis codes, free text, antidepressant/benzodiazepine prescriptions and the combinations symptom + diagnosis codes and symptom + diagnosis codes + free text, wherever relevant. Results and discussion Correlation between the HIS and INTEGO was generally high, except for anxiety. Agreement ranged from fair to poor, but increased when combining certain variables, by including free text, or by increasing the prescription frequency to resemble chronic use. Agreement remained poor when comparing questions about anxiety. Prevalences from INTEGO were mostly underestimates. Conclusion The external validity of medical registries can be poor, especially compared with survey data. A considerate choice of variables and prescription chronicity is needed to accurately use a registry as a surveillance tool for mental health.
Keywords: epidemiology; Medical Informatics; Mental health

Assessing the contribution of smoking to the disease burden in Belgium, 2013-2020 - Sarah Nayani; Robby De Pauw; Brecht Devleesschauwer; L Guariguata (European Journal of Public Health, 2024)
Keywords: burden of disease; SMOKING

Belgian national burden of disease study. Methodological framework for the projections of the non-fatal burden of disease of non-communicable diseases in Belgium. - Robby De Pauw; Brecht Devleesschauwer (Sciensano, 2024)
Keywords: burden of disease; projections; YLD

Burden of inflammatory bowel disease in Belgium, 2020 - Rani Claerman; Brecht Devleesschauwer; Sarah Nayani; Robby De Pauw (European Journal of Public Health, 2024)
Inflammatory bowel disease (IBD) comprises digestive disorders resulting from non-infectious inflammation of the colon and gastrointestinal tract. With its global prevalence on the rise, IBD poses significant challenges to healthcare systems. There is a need for more accurate disease burden estimates to guide decision-making processes within the health sector. As a part of the Belgian national burden of disease study (BeBOD), this study aims to estimate the burden of IBD in Belgium based on locally available data. We estimated the Belgian IBD burden in 2020 in terms of mortality, prevalence, years of life lost (YLLs) due to premature death, years lived with disability (YLDs), and disability-adjusted life years (DALYs). As there is no single comprehensive data source on prevalence of IBD in Belgium, a critical appraisal of existing local and national data sources was conducted. Prevalence data were combined with disability weights to yield YLDs. YLLs were calculated using the most recent Global Burden of Disease (GBD) 2019 reference life table and the number of deaths caused by non-infective IBD (ICD-10 K50-52). Cause of death data were extracted from Statbel, the Belgian statistical office. The best available data source to estimate the IBD prevalence in Belgium was a widespread network of general practitioners. The prevalence of IBD was 1.5% in 2020. The prevalence-based YLD for IBD was 220 YLDs per 100 000, while the YLL rate was 11.5 per 100 000. We estimated 26 276 DALYs caused by IBD in 2020. Of the total DALYs caused by IBD, 5% were due to YLLs and 95% were due to YLDs. Our burden estimates for IBD in Belgium were however higher than those of the GBD study. IBD imposes a low fatal burden, whereas the burden of morbidity is more prominent. Our findings could be useful for policy makers to justify and prioritize resource allocation. Integrating the current research in BeBOD will allow monitoring the burden of IBD over time. Key messages • Inflammatory bowel disease is characterized by a substantial non-fatal burden due to chronic relapsing and persistent symptoms. • National inflammatory bowel disease burden estimates are useful to guide decision-making within the health sector.
Keywords: burden of disease; inflammatory bowel disease

The burden of psoriasis in Belgium, 2021 - Rani Claerman; Brecht Devleesschauwer; Sarah Nayani; Robby De Pauw (European Journal of Public Health, 2024)
Psoriasis is a common, chronic, inflammatory skin disease with a great impact on healthcare systems. Given the limitations of the currently available burden estimates, estimates of the Belgian national burden of disease study are necessary in order to guide decision-making processes within the health sector. According to the Global Psoriasis Atlas, the prevalence of psoriasis is rising globally. The current study aims to estimate the burden of psoriasis in Belgium using national data. As there is no single comprehensive data source on prevalence of psoriasis in Belgium, a critical appraisal of existing local and national data sources was conducted. We estimated the non-fatal psoriasis burden in terms of years lived with disability (YLD). Estimated prevalence data were combined with disability weights to yield YLDs imposed by psoriasis. Mortality attributable to psoriasis was assumed to be zero, in line with the Global Burden of Disease study (GBD) 2019. We assessed three data sources containing information on existing cases with psoriasis in Belgium. Based on qualitative and quantitative appraisal, a widespread network of general practitioners was identified as the best available national data source. In 2021, the prevalence of psoriasis in Belgium was 2.1%, leading to 13084 DALYs (113 DALYs per 100 000). The burden of psoriasis was in line with national disease burden estimates for bipolar disorder, multiple myeloma, and hearing loss. Our prevalence, YLD, and DALY estimates for psoriasis in Belgium were however lower than those of the GBD study. Psoriasis imposes a non-negligible burden on population health in Belgium, despite it not being a cause of death. Along progression in psoriasis management, objective evaluation of psoriasis burden is critical to track the trends at the population level. Key messages • Psoriasis is a common skin disease with a relatively high morbidity burden. • Information on psoriasis prevalence and burden are crucial for disease management and appropriate health-care planning.
Keywords: burden of disease; psoriasis

The data layer: the importance of sources critical appraisal - Vanessa Gorasso; Laura Van den Borre; Aline Scohy; Maja Schmidt; Brecht Devleesschauwer; Robby De Pauw (European Journal of Public Health, 2024)
One of the main purposes of public health institute is to tracking the health status of its citizens and understanding its evolution over time. Given the absence of a singular, comprehensive data source, we developed a framework to select databases specific to each disease and outcome of interest. This process includes a thorough evaluation of the operational case definitions, as well as the strengths and weaknesses of each database, with a particular focus on their sensitivity and specificity. These qualities are appraised following a dedicated scoring form into different categories (i.e., high, medium, low). The selection criteria for data sources hinge on several key questions: Is the database exhaustive or merely a sample? Does the case definition rely on direct medical diagnoses or proxies? Does the source capture all cases? Is the data collected at regional or national level? Are there mechanisms for yearly or periodic updates? To establish the most accurate national prevalence estimates for each outcome, we often need to adjust for data misclassification-applying corrections for biases such as self-reported data and interpolating for missing entries. In some instances, a pooled estimate from multiple data sources is developed. A specific case will be presented to illustrate our approach in practice. This critical evaluation is pivotal, as the quality of data underpins the entire health information pyramid. The integrity of our data directly influences our ability to convert data into actionable health wisdom, ultimately affecting public health decision-making and policy formulation.
Keywords: Health monitoring

Embracing the complexity: a critical appraisal of global neck pain trends and research gaps - Robby De Pauw; Laguna, Javier Muñoz; Vanessa Gorasso (The Lancet Rheumatology, 2024)
/
Keywords: commentary; projections

Establishing disease models for the Belgian national burden of disease study: challenges and perspectives - Sarah Nayani; Brecht Devleesschauwer; Rani Claerman; Robby De Pauw (European Journal of Public Health, 2024)
Abstract The Belgian national burden of disease study (BeBOD) was launched in 2022, and currently provides disease burden estimates for 38 key diseases. The calculation of the non-fatal component of the disease burden, the Years Lived with Disability (YLD), follows a stepwise approach that aims to establish priority outcomes; quantify prevalence “best estimates”; establish disease models; and perform expert evaluation of methods and results. The disease models visualize the relationship between the different health states associated with a given outcome. Health states include the different acute and chronic stages of the outcome (including complications), which may be stratified in different severity levels (e.g., mild, moderate, severe). Disease models used in burden of disease studies primarily aim to document the considered health states, and do not aim at a representation of the complete clinical picture of the condition. The disease models instead help in understanding how the number of cases for each health state is calculated. Models typically start with one “parent node”, which contains all cases. This parent node then gives rise to multiple “child nodes”, with the terminal child nodes representing the individual health states. In BeBOD, disease models and severity distributions are adapted from the Global Burden of Disease (GBD) study, and complemented with local data where possible. This process ensures consistency with available disability weights, while still allowing for local data to feed into the calculations. In this presentation, we will demonstrate the BeBOD process for establishing disease models based on a number of archetypical examples, which represent varying challenges linked to disease model complexity, clarity and completeness of the GBD disease model documentation, and availability of local data. Future perspectives will be discussed, including the improved leveraging of local clinical data, and the implementation of tailored active data collection.
Keywords: burden of disease

The information layer: shaping data into meaning with interactive tools - Masja Schmidt; Vanessa Gorasso; Laura Van den Borre; Aline Scohy; Brecht Devleesschauwer; Robby De Pauw (European Journal of Public Health, 2024)
Valorization and interpretation of health data are contingent upon a robust analytical framework. This framework encompasses essential processes such as data cleaning, validation, and the critical evaluation of bias and missing data. A nuanced understanding of these factors is crucial for contextualizing data through stratification, developing comprehensive analysis plans, and addressing interactions, covariates, and confounders. Such meticulous methodologies guard against ‘data fishing expeditions’ that could otherwise lead to erroneous conclusions. Healthybelgium.be exemplifies our approach for deciding on appropriate levels of data aggregation and stratification. This study serves as a foundation for deriving conclusions and formulating hypotheses regarding the health status of the national and various sub-populations. Our discussion will cover the limitations of the questions that can be answered with the available data, the resulting opportunities for data enhancement, and the subsequent valorization of findings for knowledge advancement. Furthermore, we will present the interactive tools (through the use of R Shiny) developed by Sciensano to disseminate information broadly, making it accessible and comprehensible to diverse audiences. These tools embody a balance of strength and limitation, facilitating an informed dialogue among stakeholders. The ongoing refinement of these tools, influenced by continuous learning and insights, exemplifies our commitment to evolving public health intelligence.
Keywords: Health monitoring; interactive tools

The knowledge layer: the role of key messages for translating data into meaning - Aline Scohy; Vanessa Gorasso; Laura Van den Borre; Maja Schmidt; Brecht Devleesschauwer; Robby De Pauw (European Journal of Public Health, 2024)
The large volume of data generated by health information systems often remains siloed within the institutions that produce it, posing significant challenges to its reuse and interpretation. This fragmentation can result in conflicting information on critical health topics, complicating the decision-making process for policymakers. To address this issue, Belgium has initiated the ‘Health Status Report’ website, hosted at healthybelgium.be. This website aims to synthesize and present health data in a manner that supports evidence-based policy formulation. The website adopts a structured approach to data integration and interpretation: initially, we identify and prioritize key health topics based on their relevance and the quality of available data. Subsequently, we merge and analyze data from diverse sources to discern patterns and trends that are crucial for public health monitoring. The insights gained are then presented through both narrative texts and interactive visualizations, facilitating access and understanding for a broad audience. Crucial to this process is ongoing communication with experts and stakeholders, ensuring that the data is not only accurately interpreted but also aligns with the needs and expectations of its users. We also aim to translate the raw data into meaningful key messages by consulting with internal and external experts. This interactive platform thus serves as a critical tool for translating complex health data into actionable knowledge, enabling informed public health strategies and interventions.
Keywords: Health monitoring; Knowledge translation

Rising socioeconomic disparities in childhood overweight and obesity in Belgium - Sabine Drieskens; Rana Charafeddine; Stefanie Vandevijvere; Robby De Pauw; Stefaan Demarest (Archives of Public Health, 2024)
Keywords: CHILDREN; health interview survey; Obesity; Overweight; Socioeconomic inequalities

Sociodemographic and socioeconomic disparities in COVID-19 vaccine uptake in Belgium: a nationwide record linkage study - Lisa Cavillot; Joris Van Loenhout; Brecht Devleesschauwer; Chloé Wyndham-Thomas; Herman Van Oyen; Jinane Ghattas; Koen Blot; Laura Van den Borre; Matthieu Billuart; Niko Speybroeck; Robby De Pauw; Veerle Stouten; et al. (Journal of Epidemiology and Community Health, 2024)
Background Recent studies have identified important social inequalities in SARS-CoV-2 infections and related COVID-19 outcomes in the Belgian population. The aim of our study was to investigate the sociodemographic and socioeconomic characteristics associated with the uptake of COVID-19 vaccine in Belgium. Methods We conducted a cross-sectional analysis of the uptake of a first COVID-19 vaccine dose among 5 342 110 adults (≥18 years) in Belgium on 31 August 2021. We integrated data from four national data sources: the Belgian vaccine register (vaccination status), COVID-19 Healthdata (laboratory test results), DEMOBEL (sociodemographic/socioeconomic data) and the Common Base Register for HealthCare Actors (individuals licensed to practice a healthcare profession in Belgium). We used multivariable logistic regression analysis for identifying characteristics associated with not having obtained a first COVID-19 vaccine dose in Belgium and for each of its three regions (Flanders, Brussels and Wallonia). Results During the study period, 10% (536 716/5 342 110) of the Belgian adult population included in our study sample was not vaccinated with a first COVID-19 vaccine dose. A lower COVID-19 vaccine uptake was found among young individuals, men, migrants, single parents, one-person households and disadvantaged socioeconomic groups (with lower levels of income and education, unemployed). Overall, the sociodemographic and socioeconomic disparities were comparable for all regions. Conclusions The identification of sociodemographic and socioeconomic disparities in COVID-19 vaccination uptake is critical to develop strategies guaranteeing a more equitable vaccination coverage of the Belgian adult population.
Keywords: COVID-19; Social inequalities; vaccination coverage

The Spider: a visual, multisystemic symptom impact questionnaire for people with hypermobility-related disorders-validation in adults. - E R Ewer; Robby De Pauw; H Kazkazk; N Ninis; P Rowe; J V Simmonds; I De Wandele (Clin Rheumatol, 2024)
INTRODUCTION: Hypermobility spectrum disorders (HSD) and hypermobile Ehlers-Danlos syndrome (hEDS) are often accompanied by varied and complex multisystemic comorbid symptoms/conditions. The Spider questionnaire was developed to evaluate the presence and impact of eight common multisystemic comorbidities. Thirty-one questions across eight symptom domains assess neuromusculoskeletal, pain, fatigue, cardiac dysautonomia, urogenital, gastrointestinal, anxiety, and depression symptoms. This study aimed to evaluate the Spider's construct validity in adults. METHOD: A cross-sectional observational study was conducted over four stages. Three international patient charities aided recruitment of participants through social media and website advertisements. Adults aged 18 to 65 years, with and without HSD/hEDS, were invited to participate. Validated, frequently used comparator questionnaires were used to establish convergent validity of Spider symptom domains. A control group was recruited for known-group validity analysis. Participants answered each Spider domain and the corresponding comparator questionnaire via surveys hosted by REDCap. Anonymous data were analysed using SPSS. Convergent validity was assessed through Spearman's correlational analysis and known-group validity through Mann-Whitney U analysis. RESULTS: A total of 11,151 participants were recruited across the four stages. Statistically significant, moderate-to-strong correlations were found between all Spider domains and their comparators (p < 0.001, r = 0.63 to 0.80). Known-group validity analysis showed statistically significant differences (p < 0.001) between the hypermobile and control groups in all eight domains. CONCLUSIONS: Convergent and known-group validity of the Spider was established with adults. These results suggest the Spider can measure the presence and impact of multisystemic comorbid symptoms/conditions in adults with HSD/hEDS, providing a tool which guides multidisciplinary management. Key Points • The Spider questionnaire is a novel tool assessing the presence and impact of the multisystemic comorbid symptoms/conditions associated with HSD/hEDS. • Convergent and known-group validity of the Spider questionnaire was established in adults aged 18 to 65. • This tool provides a quick and easy method to visualise the symptom profile of those with HSD/hEDS to guide symptom management.
Keywords: ADOLESCENT; Adult; Aged; Anxiety; comorbidity; cross-sectional studies; dépression; Ehlers-Danlos Syndrome; Fatigue; Female; Humans; Joint Instability; Male; middle aged; Primary Dysautonomias; Reproducibility of Results; Surveys and Questionnaires; Young adult

Unraveling social health inequalities during COVID-19 in Belgium: the vital role of data linkages - Laura Van den Borre; Lisa Cavillot; Robby De Pauw; Brecht Devleesschauwer (European Journal of Public Health, 2024)
Background During the COVID-19 crisis, data linkages were set up to efficiently monitor the outbreak and identify vulnerable population groups. Yet, considerable technical, administrative and data security issues have hindered the effectiveness of data linkages as a critical instrument during public health emergencies. This workshop aims to provide a practical demonstration of the challenges encountered in a Belgian data linkage during the COVID-19 crisis, along with the strategies implemented to overcome these challenges. This case study offers insights into the development of a highly sensitive linkage between COVID-19 hospital data and information related to social and health use in Belgium. Methods The HELICON data linkage is developed at the individual level to investigate the risk of COVID-19 hospitalization and the influence of various social and biomedical factors during and after the crisis. Data are drawn from data collections on hospitalization from the COVID-19 health surveillance (Sciensano), on the socioeconomic and sociodemographic context (Statistics Belgium), and on healthcare use and reimbursement (InterMutualistic Agency). Results A representative case-cohort study is established comprising 1,149,264 million randomly selected Belgians and 44,508 hospitalized patients. Annual follow-up is scheduled over a four-year span, allowing the investigation of pre- and post-pandemic health data from July 2020 to January 2026. Conclusions The HELICON data linkage took 3.5 years to complete. Among the many challenges, we were faced with complicated approval procedures, ambiguous data security guidelines, unclear cost estimates, and technical issues related to the analysis environment. Building on these experiences, we explore the strengths and weaknesses of data linkages as a research instrument during the COVID-19 pandemic and discuss which lessons should be drawn to for the post-pandemic era.
Keywords: COVID-19; Social inequalities

The wisdom layer: how to support evidence-informed policymaking - Laura Van den Borre; Vanessa Gorasso; Aline Scohy; Masja Schmidt; Brecht Devleesschauwer; Robby De Pauw (European Journal of Public Health, 2024)
One of the returning challenges faced by public health scientists is bridging the ‘evidence-policy gap’-the disparity between identifying public health issues and implementing policies to address them. Despite the extensive literature documenting the challenges of promoting evidence-informed policymaking, opportunities for researchers to exchange experiences and learn from each other’s failures are limited. This presentation seeks to: (a) analyze key concepts in evidence-informed policymaking, based on the health information pyramid; (b) identify obstacles and facilitators in the translation of knowledge into actionable policy; and (c) present both successful and unsuccessful examples from our initiatives to influence health policy in Belgium. Specifically, we will discuss the concrete impact of the Belgian Health Status Report and the role this report plays in the development of actionable health objectives for Belgium. We will also cover the role of healthybelgium.be in governing and monitoring the health status of the Belgian population by discussing why this website has been recognized by WHO Europe as a model of good practice in evidence-informed policymaking.
Keywords: Health information; Knowledge translation

Women's health report, Belgium 2024 - Aline Scohy; Eduardo Bracho Montes de Oca; Rani Claerman; Robby De Pauw; Leonor Guariguata; Laura Int Panis; Gaelle Mogin; Sarah Nayani; Masja Schmidt; Laura Van den Borre; Vanessa Gorasso (Sciensano, 2024)
Keywords: Gender; Health Status Indicators

Association between SARS-CoV-2 variants and post COVID-19 condition: findings from a longitudinal cohort study in the Belgian adult population - Huyen Nguyen Thi Khanh; Laura Cornelissen; Diego Castanares-Zapatero; Robby De Pauw; Dieter Van Cauteren; Stefaan Demarest; Sabine Drieskens; Brecht Devleesschauwer; Karin De Ridder; Rana Charafeddine; Pierre Smith (BMC Infect Dis, 2023)
BACKGROUND: While many studies on the determinants of post-COVID-19 conditions (PCC) have been conducted, little is known about the relationship between SARS-CoV-2 variants and PCC. This study aimed to assess the association between different SARS-CoV-2 variants and the probability of having PCC three months after the infection. METHODS: This study was a longitudinal cohort study conducted between April 2021 and September 2022 in Belgium. In total, 8,238 adults with a confirmed SARS-CoV-2 infection were followed up between the time of their infection and three months later. The primary outcomes were the PCC status three months post infection and seven PCC symptoms categories (neurocognitive, autonomic, gastrointestinal, respiratory, musculoskeletal, anosmia and/or dysgeusia, and other manifestations). The main exposure variable was the type of SARS-CoV-2 variants (i.e. Alpha, Delta, and Omicron), extracted from national surveillance data. The association between the different SARS-CoV-2 variants and PCC as well as PCC symptoms categories was assessed using multivariable logistic regression. RESULTS: The proportion of PCC among participants infected during the Alpha, Delta, and Omicron-dominant periods was significantly different and respectively 50%, 50%, and 37%. Participants infected during the Alpha- and Delta-dominant periods had a significantly higher odds of having PCC than those infected during the Omicron-dominant period (OR = 1.61, 95% confidence interval [CI] = 1.33-1.96 and OR = 1.73, 95%CI = 1.54-1.93, respectively). Participants infected during the Alpha and Delta-dominant periods were more likely to report neurocognitive, respiratory, and anosmia/dysgeusia symptoms of PCC. CONCLUSIONS: People infected during the Alpha- and Delta-dominant periods had a higher probability of having PCC three months after infection than those infected during the Omicron-dominant period. The lower probability of PCC with the Omicron variant must also be interpreted in absolute figures. Indeed, the number of infections with the Omicron variant being higher than with the Alpha and Delta variants, it is possible that the overall prevalence of PCC in the population increases, even if the probability of having a PCC decreases.
Keywords: long COVID; post-COVID-19 condition; SARS-CoV-2 variants

Belgian general practitioners’ perception and use of physical activity on prescription - Sherihane Bensemmane; Robby De Pauw; Hans Keune; Robrecht De Schreye (European Journal of Public Health, 2023)
Background Physical activity (PA) reduces 19.5% of the attributable burden of chronic diseases (CDs), i.e. healthy life years lost due to morbidity and mortality. In addition, 29.5% of Belgians self-declared having at least one chronic disease. Moreover, almost 30% of the population above 15 years old is at health risk due to physical inactivity. Evidence shows physical activity on prescription (PAP) has a positive impact on PA level and metabolic health. General Practitioners (GPs) can use PAP as a prevention intervention. In Belgium, overall 94,1% of citizens have a referring General Practitioner (GP) or are affiliated with a general practice. There is no national policy on PAP, only a regional policy in Flanders. Therefore, the aim of the study is to investigate the perception and the (potential) provision of PAP by Belgian GPs. Methods A cross-sectional survey was conducted in Belgian GPs between January and end of March 2023. The survey has 41 (ordinal or multiple choice) questions. Descriptive statistics were performed. Results 134 GPs completed the survey of which 56% were female. 66.4% work in Flanders, 19.4% in Wallonia and 14.2% in Brussels-Capital region. Among respondents, 44% only discuss the benefits of PA with patients with a CD. Interestingly, less than 2% never discuss PA. 86.8% (would) prescribe if patients’ health status would be remedied by increasing PA, while 35.8% (would) use PAP if patients are inactive, regardless of their health status. About 75% identified chronic disease and exercise initiation as incentives for PAP. 41% would refer to PA (motivational) coaches, 55.2% to (adapted) PA courses. Lack of training (12.7%), time (49.3%), and knowledge of local PA offer (74%) were cited as barriers to using PAP. Conclusions The majority of responding GPs linked PAP with CD. Although there is no national implementation and regulation of PAP, GPs used (were ready to use) PAP in their practice. However, several barriers still hinder the use of PAP.
Keywords: chronic diseases; general practitioners; Physical activity; Prescription

Belgian national burden of disease study. Guidelines for the calculation of DALYs in Belgium - Robby De Pauw; Vanessa Gorasso; Brecht Devleesschauwer (Sciensano, 2023)
Keywords: burden of disease; Burden of disease methodology; DALYs

Belgian National Burden of Disease Study. Guidelines for the calculation of Disability-Adjusted Life Years in Belgium, September 2023 - Robby De Pauw; Vanessa Gorasso; Aline Scohy; Laura Van den Borre; Brecht Devleesschauwer (Sciensano, 2023)
Keywords: burden of disease; Burden of disease methodology; DALYs

Belgian national burden of disease study. Methodological framework for cost estimation - Masja Schmidt; Vanessa Gorasso; Robby De Pauw; Brecht Devleesschauwer (Sciensano, 2023)
Keywords: BeBOD; Cost of Illness

The Belgian physiotherapy reimbursement criteria for fall prevention fails in screening appropriately fall-prone community-dwelling older adults - Ellis Rommers; Mirko Petrovic; Robby De Pauw; Anke Van Bladel; Dirk Cambier (Acta Clin Belg, 2023)
OBJECTIVES: The incidence of falling in older adults has remained unchanged over the past decades, despite evidence-based prevention initiatives. Therefore, it is appropriate to reflect on the current screening approach for preventive initiatives. The objective of this study was to determine whether the multifactorial algorithm proposed by Lusardi et al. (2017) exhibits superior predictive validity compared to the currently employed algorithm by the Belgian National Institute for Health and Disability Insurance (NIHDI). METHODS: The current study includes a secondary analysis of data collected from a falls-related study in the Department of Rehabilitation Sciences at Ghent University to compare the predictive validity of the two algorithms. Sensitivity, specificity, positive and negative predictive value and area under the curve (AUC) were calculated to ascertain which algorithm is more accurate. RESULTS: The database included a total of 94 community-dwelling older adults (mean age 76 years ±7.4, 35% male). Thirty-nine participants experienced at least one fall in the 8 month follow up. Lusardi's approach has a higher sensitivity score (89.7% compared to 10.3%) and negative predictive value (89.9% compared to 61.1%), but a lower specificity score (61.8% compared to 100%) and positive predictive value (62.2% compared to 100%) than the NIHDI approach. The AUC is 0.76 for Lusardi's approach and 0.55 for the NIHDI approach. CONCLUSION: The use of the multifactorial algorithm proposed by Lusardi et al. may be significant and more accurate in identifying adults at risk to falls. Further research is needed particularly with a larger, more heterogenous group of older adults.
Keywords: Falls; Falls risk; older adults; Physiotherapy; Prediction

Certainty of the Global Burden of Disease 2019 modelled prevalence estimates for musculoskeletal conditions: A meta-epidemiological study - Javier Muñoz Laguna; Milo A Puhan; Fernando Rodríguez Artalejo; Robby De Pauw; Grant M A Wyper; Brecht Devleesschauwer; João Vasco Santos; Cesar A Hincapié (Int J Public Health, 2023)
To describe and assess the risk of bias of the primary input studies that underpinned the Global Burden of Disease Study (GBD) 2019 modelled prevalence estimates of low back pain (LBP), neck pain (NP), and knee osteoarthritis (OA), from Australia, Brazil, Canada, Spain, and Switzerland. To evaluate the certainty of the GBD modelled prevalence evidence. Primary studies were identified using the GBD Data Input Sources Tool and their risk of bias was assessed using a validated tool. We rated the certainty of modelled prevalence estimates based on the GRADE Guidelines 30-the GRADE approach for modelled evidence. Seventy-two primary studies (LBP: 67, NP: 2, knee OA: 3) underpinned the GBD estimates. Most studies had limited representativeness of their study populations, used suboptimal case definitions and applied assessment instruments with unknown psychometric properties. The certainty of modelled prevalence estimates was low, mainly due to risk of bias and indirectness. Beyond the risk of bias of primary input studies for LBP, NP, and knee OA in GBD 2019, the certainty of country-specific modelled prevalence estimates still have room for improvement.
Keywords: epidemiology; Global Burden of Disease; GRADE approach; knee osteoarthritis; Low Back Pain; Musculoskeletal disorders; neck pain; prevalence

Classification of post COVID-19 condition symptoms: a longitudinal study in the Belgian population - Sarah Nayani; Diego Castanares-Zapatero; Robby De Pauw; Dieter Van Cauteren; Stefaan Demarest; Sabine Drieskens; Laura Cornelissen; Brecht Devleesschauwer; Karin De Ridder; Rana Charafeddine; Pierre Smith (BMJ Open, 2023)
Objectives Since the onset of the COVID-19 pandemic, most research has focused on its acute pathophysiology, yet some people tend to experience persisting symptoms beyond the acute phase of infection, referred to as post COVID-19 condition (PCC). However, evidence on PCC is still scarce. This study aimed to assess the distribution, classification of symptoms and associated factors of PCC in adults. Design Longitudinal online cohort study. Setting National study in Belgium. Participants Participants were Belgian adults with a recent SARS-CoV-2 infection and were recruited when called up for contact tracing. A total of 3039 participants were included and completed an online questionnaire at the time of their infection and again 3 months later. Outcome measures The baseline questionnaire assessed the initial health status of the participants and their status during the acute phase of the infection. The follow-up questionnaire assessed their PCC status 3 months after infection. A latent class analysis (LCA) was performed to assess whether there are different classes of individuals with a similar set of self-reported PCC symptoms. Results Half of the participants reported PCC 3 months after infection (47%). The most frequent symptoms were fatigue (21%), headache (11%) and memory problems (10%). The LCA highlighted three different classes of PCC symptoms with different risk factors: (1) a combination of loss of smell and taste, (2) a combination of neurological symptoms and (3) other heterogeneous symptoms. Conclusions With the increasing number of people who underwent COVID-19, PCC has become an important but complex public health problem due to the heterogeneity of its symptoms. The classification of symptoms performed in this study can help give insight into different aetiologies of PCC and better plan care according to the symptoms and needs of those affected.

The direct disease burden of COVID-19 in Belgium in 2020 and 2021 - Robby De Pauw; Brecht Devleesschauwer; Lander Willem; Jure Jurcevic; Pierre Smith; Aline Scohy; Grant M A Wyper; Sara Monteiro Pires; Nina Van Goethem; Philippe Beutels; Nicolas Franco; Steven Abrams; et al. (BMC Public Health, 2023)
BACKGROUND: Burden of disease estimates have become important population health metrics over the past decade to measure losses in health. In Belgium, the disease burden caused by COVID-19 has not yet been estimated, although COVID-19 has emerged as one of the most important diseases. Therefore, the current study aims to estimate the direct COVID-19 burden in Belgium, observed despite policy interventions, during 2020 and 2021, and compare it to the burden from other causes. METHODS: Disability-adjusted life years (DALYs) are the sum of Years Lived with Disability (YLDs) and Years of Life Lost (YLLs) due to disease. DALYs allow comparing the burden of disease between countries, diseases, and over time. We used the European Burden of Disease Network consensus disease model for COVID-19 to estimate DALYs related to COVID-19. Estimates of person-years for (a) acute non-fatal disease states were calculated from a compartmental model, using Belgian seroprevalence, social contact, hospital, and intensive care admission data, (b) deaths were sourced from the national COVID-19 mortality surveillance, and (c) chronic post-acute disease states were derived from a Belgian cohort study. RESULTS: In 2020, the total number of COVID-19 related DALYs was estimated at 253,577 [252,541 - 254,739], which is higher than in 2021, when it was 139,281 [136,704 - 142,306]. The observed COVID-19 burden was largely borne by the elderly, and over 90% of the burden was attributable to premature mortality (i.e., YLLs). In younger people, morbidity (i.e., YLD) contributed relatively more to the DALYs, especially in 2021, when vaccination was rolled out. Morbidity was mainly attributable to long-lasting post-acute symptoms. CONCLUSION: COVID-19 had a substantial impact on population health in Belgium, especially in 2020, when COVID-19 would have been the main cause of disease burden if all other causes had maintained their 2019 level.
Keywords: burden of disease; COVID-19; Disability-Adjusted Life Years; Years lived with disability; Years of life lost

Evaluating the health and health economic impact of the COVID-19 pandemic on delayed cancer care in Belgium: A Markov model study protocol - Yasmine Khan; Nick Verhaeghe; Robby De Pauw; Brecht Devleesschauwer; Sylvie Gadeyne; Vanessa Gorasso; Yolande Lievens; Niko Speybroek; Nancy Vandamme; Miet Vandemaele; Laura Van den Borre; Sophie Vandepitte; et al. (PLoS One, 2023)
INTRODUCTION: Cancer causes a substantial burden to our society, both from a health and an economic perspective. To improve cancer patient outcomes and lower society expenses, early diagnosis and timely treatment are essential. The recent COVID-19 crisis has disrupted the care trajectory of cancer patients, which may affect their prognosis in a potentially negative way. The purpose of this paper is to present a flexible decision-analytic Markov model methodology allowing the evaluation of the impact of delayed cancer care caused by the COVID-19 pandemic in Belgium which can be used by researchers to respond to diverse research questions in a variety of disruptive events, contexts and settings. METHODS: A decision-analytic Markov model was developed for 4 selected cancer types (i.e. breast, colorectal, lung, and head and neck), comparing the estimated costs and quality-adjusted life year losses between the pre-COVID-19 situation and the COVID-19 pandemic in Belgium. Input parameters were derived from published studies (transition probabilities, utilities and indirect costs) and administrative databases (epidemiological data and direct medical costs). One-way and probabilistic sensitivity analyses are proposed to consider uncertainty in the input parameters and to assess the robustness of the model's results. Scenario analyses are suggested to evaluate methodological and structural assumptions. DISCUSSION: The results that such decision-analytic Markov model can provide are of interest to decision makers because they help them to effectively allocate resources to improve the health outcomes of cancer patients and to reduce the costs of care for both patients and healthcare systems. Our study provides insights into methodological aspects of conducting a health economic evaluation of cancer care and COVID-19 including insights on cancer type selection, the elaboration of a Markov model, data inputs and analysis.
Keywords: Belgium; Cost-Benefit Analysis; COVID-19; Delivery of Health Care; Humans; Markov Chains; Models, Economic; Neoplasms; Pandemics; Quality-Adjusted Life Years

The health and economic burden of musculoskeletal disorders in Belgium from 2013 to 2018 - Vanessa Gorasso; Johan Van der Heyden; Robby De Pauw; Ingrid Pelgrims; Eva M De Clercq; Karin De Ridder; Stefanie Vandevijvere; Stijn Vansteelandt; Bert Vaes; Delphine De Smedt; Brecht Devleesschauwer (Popul Health Metr, 2023)
INTRODUCTION: Low back pain (LBP), neck pain (NKP), osteoarthritis (OST) and rheumatoid arthritis (RHE) are among the musculoskeletal (MSK) disorders causing the greatest disability in terms of Years Lived with Disability. The current study aims to analyze the health and economic impact of these MSK disorders in Belgium, providing a summary of morbidity and mortality outcomes from 2013 to 2018, as well as direct and indirect costs from 2013 to 2017. METHODS: The health burden of LBP, NKP, OST and RHE in Belgium from 2013 to 2018 was summarized in terms of prevalence and disability-adjusted life years (DALY) using data from the Belgian health interview surveys (BHIS), the INTEGO database (Belgian registration network for general practitioners) and the Global Burden of Diseases study 2019. The economic burden included estimates of direct medical costs and indirect costs, measured by cost of work absenteeism. For this purpose, data of the respondents to the BHIS-2013 were linked with the national health insurance data (intermutualistic agency [IMA] database) 2013-2017. RESULTS: In 2018, 2.5 million Belgians were affected by at least one MSK disorder. OST represented the disorder with the highest number of cases for both men and women, followed by LBP. In the same year, MSK disorders contributed to a total of 180,746 DALYs for female and 116,063 DALYs for men. LBP appeared to be the largest contributor to the health burden of MSK. Having at least one MSK disorder costed on average 3 billion € in medical expenses and 2 billion € in indirect costs per year, with LBP being the most costly. CONCLUSION: MSK disorders represent a major health and economic burden in Belgium. As their burden will probably continue to increase in the future, acting on the risk factors associated to these disorders is crucial to mitigate both the health and economic burden.
Keywords: Absenteeism costs; Disability-Adjusted Life Years; Healthcare costs; Musculoskeletal disorders

Investigating years of life lost in Belgium, 2004-2019: A comprehensive analysis using a probabilistic redistribution approach - Brecht Devleesschauwer; Aline Scohy; Robby De Pauw; Vanessa Gorasso; Anne Kongs; Elias Neirynck; Peter Verduyckt; Grant M A Wyper; Laura Van den Borre (Arch Public Health, 2023)
INTRODUCTION: Information on years of life lost (YLL) due to premature mortality is instrumental to assess the fatal impact of disease and necessary for the calculation of Belgian disability-adjusted life years (DALYs). This study presents a novel method to reallocate causes of death data. MATERIALS AND METHODS: Causes of death data are provided by Statistics Belgium (Statbel). First, the specific ICD-10 codes that define the underlying cause of death are mapped to the GBD cause list. Second, ill-defined deaths (IDDs) are redistributed to specific ICD-10 codes. A four-step probabilistic redistribution was developed to fit the Belgian context: redistribution using predefined ICD codes, redistribution using multiple causes of death data, internal redistribution, and redistribution to all causes. Finally, we used the GBD 2019 reference life table to calculate Standard Expected Years of Life Lost (SEYLL). RESULTS: In Belgium, between 2004 and 2019, IDDs increased from 31 to 34% of all deaths. The majority was redistributed using predefined ICD codes (14-15%), followed by the redistribution using multiple causes of death data (10-12%). The total number of SEYLL decreased from 1.83 to 1.73 million per year. In 2019, the top cause of SEYLL was lung cancer with a share of 8.5%, followed by ischemic heart disease (8.1%) and Alzheimer's disease and other dementias (5.7%). All results are available in an online tool https://burden.sciensano.be/shiny/mortality2019/ . CONCLUSION: The redistribution process assigned a specific cause of death to all deaths in Belgium, making it possible to investigate the full mortality burden for the first time. A large number of estimates were produced to estimate SEYLL by age, sex, and region for a large number of causes of death and every year between 2004 and 2019. These estimates are important stepping stones for future investigations on Disability-Adjusted Life Years (DALYs) in Belgium.
Keywords: Belgium; burden of disease; Cause of Death; Garbage code; Ill-defined death; mortality; Redistribution; Years of life lost

Post COVID-19 condition and health-related quality of life: a longitudinal cohort study in the Belgian adult population - Pierre Smith; Robby De Pauw; Dieter Van Cauteren; Stefaan Demarest; Sabine Drieskens; Laura Cornelissen; Brecht Devleesschauwer; Karin De Ridder; Rana Charafeddine (BMC Public Health, 2023)
Background Since the onset of the COVID-19 pandemic, most research has focused on the acute phase of COVID-19, yet some people experience symptoms beyond, referred to as post COVID-19 conditions (PCC). However, evidence on PCC and its impacts on health-related quality of life (HRQoL) is still scarce. This study aimed to assess the impact of COVID-19 and PCC on HRQoL. Methods This is a longitudinal cohort study of the Belgian adult population with recent SARS-CoV-2 infection. In total, 5,727 people were followed up between the time of their infection and three months later. HRQoL was measured with the EQ-5D-5L questionnaire before and during the infection and three months later. Linear mixed regression models were built to assess the longitudinal association between participants’ characteristics and the evolution of their HRQoL. Results This study found a significant decline in HRQoL during the SARS-CoV-2 infection in comparison to the situation before (β=-9.91, 95%CI=-10.13;-9.85), but no clinically important difference three months after the infection compared to the situation before, except among people reporting PCC (β=-11.15, 95%CI=-11.72;-10.51). The main symptoms of PCC with a significant negative impact on the different dimensions of HRQoL were fatigue/exhaustion (21%), headache (11%), memory problems (10%), shortness of breath (9%), and joint (7%) or muscle pain (6%). The dimension of HRQoL most negatively affected by several PCC symptoms was pain/discomfort. Conclusions With the growing number of people infected with SARS-CoV-2, PCC and its impact on HRQoL are becoming important public health issues. To allow people with PCC to recover and to limit its detrimental impact on HRQoL, it is essential to manage its various heterogeneous symptoms using a multidisciplinary approach.
Keywords: Belgium; long COVID; Quality of Life

Remarkable fungal biodiversity on northern Belgium bats and hibernacula - Pierre Becker; Claudia Van den Eynde; F. Baert; Elizabet D'hooge; Robby De Pauw; Normand, Anne-Cécile; Piarroux, Renaud; Dirk Stubbe (Mycologia, 2023)
Bats can be affected by fungal pathogens such as Pseudogymnoascus destructans, the causative agent of the white-nose syndrome. Their body surface can also be colonized by fungal commensals or carry transient fungal species and participate in their dispersal. In this study, 114 bat specimens belonging to seven species were sampled from various locations in northern Belgium. Culture-based methods revealed an important mycological diversity, with a total of 209 different taxa out of the 418 isolates. Overall, a mean of 3.7 taxa per bat was recorded, but significant differences were observed between sampling sites and seasons. The mycobiomes were dominated by cosmopolitan and plant-associated species, in particular from the genera Cladosporium, Penicillium, and Aspergillus. Other species known to be related to bats or their environment, such as Apiotrichum otae, were also retrieved. Sampling of hibernacula indicated that diverse fungal species can inhabit these sites, including a yet undescribed Pseudogymnoascus species, distinct from Ps. destructans, namely, Ps. cavicola.
Keywords: Mycobiome; Pseudogymnoascus cavicola; Pseudogymnoascus destructans; white-nose syndrome

Remarkable fungal biodiversity on northern Belgium bats and hibernacula. - Pierre Becker; Claudia Van den Eynde; F. Baert; Elizabet D'hooge; Robby De Pauw; Normand, Anne-Cécile; Piarroux, Renaud; Dirk Stubbe (Mycologia, 2023)
Bats can be affected by fungal pathogens such as , the causative agent of the white-nose syndrome. Their body surface can also be colonized by fungal commensals or carry transient fungal species and participate in their dispersal. In this study, 114 bat specimens belonging to seven species were sampled from various locations in northern Belgium. Culture-based methods revealed an important mycological diversity, with a total of 209 different taxa out of the 418 isolates. Overall, a mean of 3.7 taxa per bat was recorded, but significant differences were observed between sampling sites and seasons. The mycobiomes were dominated by cosmopolitan and plant-associated species, in particular from the genera , and . Other species known to be related to bats or their environment, such as , were also retrieved. Sampling of hibernacula indicated that diverse fungal species can inhabit these sites, including a yet undescribed species, distinct from , namely, .
Keywords: Animals; Belgium; biodiversity; Chiroptera; Mycoses; Penicillium

Social inequalities and long-term health impact of COVID-19 in Belgium: protocol of the HELICON population data linkage - Robby De Pauw; Laura Van den Borre; Youri Baeyens; Lisa Cavillot; Sylvie Gadeyne; Jinane Ghattas; Delphine De Smedt; David Jaminé; Yasmine Khan; Patrick Lusyne; Niko Speybroeck; Judith Racape; et al. (BMJ Open, 2023)
INTRODUCTION: Data linkage systems have proven to be a powerful tool in support of combating and managing the COVID-19 pandemic. However, the interoperability and the reuse of different data sources may pose a number of technical, administrative and data security challenges. METHODS AND ANALYSIS: This protocol aims to provide a case study for linking highly sensitive individual-level information. We describe the data linkages between health surveillance records and administrative data sources necessary to investigate social health inequalities and the long-term health impact of COVID-19 in Belgium. Data at the national institute for public health, Statistics Belgium and InterMutualistic Agency are used to develop a representative case-cohort study of 1.2 million randomly selected Belgians and 4.5 million Belgians with a confirmed COVID-19 diagnosis (PCR or antigen test), of which 108 211 are COVID-19 hospitalised patients (PCR or antigen test). Yearly updates are scheduled over a period of 4 years. The data set covers inpandemic and postpandemic health information between July 2020 and January 2026, as well as sociodemographic characteristics, socioeconomic indicators, healthcare use and related costs. Two main research questions will be addressed. First, can we identify socioeconomic and sociodemographic risk factors in COVID-19 testing, infection, hospitalisations and mortality? Second, what is the medium-term and long-term health impact of COVID-19 infections and hospitalisations? More specific objectives are (2a) To compare healthcare expenditure during and after a COVID-19 infection or hospitalisation; (2b) To investigate long-term health complications or premature mortality after a COVID-19 infection or hospitalisation; and (2c) To validate the administrative COVID-19 reimbursement nomenclature. The analysis plan includes the calculation of absolute and relative risks using survival analysis methods. ETHICS AND DISSEMINATION: This study involves human participants and was approved by Ghent University hospital ethics committee: reference B.U.N. 1432020000371 and the Belgian Information Security Committee: reference Beraadslaging nr. 22/014 van 11 January 2022, available via https://www.ehealth.fgov.be/ehealthplatform/file/view/AX54CWc4Fbc33iE1rY5a?filename=22-014-n034-HELICON-project.pdf. Dissemination activities include peer-reviewed publications, a webinar series and a project website.The pseudonymised data are derived from administrative and health sources. Acquiring informed consent would require extra information on the subjects. The research team is prohibited from gaining additional knowledge on the study subjects by the Belgian Information Security Committee's interpretation of the Belgian privacy framework.
Keywords: Belgium; Cohort Studies; COVID-19; COVID-19 Testing; Humans; Pandemics; SARS-CoV-2

Sociodemographic and socioeconomic disparities in COVID-19 vaccine uptake in Belgium: a nationwide record linkage study. - Lisa Cavillot; Joris Van Loenhout; Brecht Devleesschauwer; Chloé Wyndham-Thomas; Herman Van Oyen; Jinane Ghattas; Koen Blot; Laura Van den Borre; Matthieu Billuart; Niko Speybroeck; Robby De Pauw; Veerle Stouten; et al. (J Epidemiol Community Health, 2023)
BACKGROUND: Recent studies have identified important social inequalities in SARS-CoV-2 infections and related COVID-19 outcomes in the Belgian population. The aim of our study was to investigate the sociodemographic and socioeconomic characteristics associated with the uptake of COVID-19 vaccine in Belgium. METHODS: We conducted a cross-sectional analysis of the uptake of a first COVID-19 vaccine dose among 5 342 110 adults (≥18 years) in Belgium on 31 August 2021. We integrated data from four national data sources: the Belgian vaccine register (vaccination status), COVID-19 Healthdata (laboratory test results), DEMOBEL (sociodemographic/socioeconomic data) and the Common Base Register for HealthCare Actors (individuals licensed to practice a healthcare profession in Belgium). We used multivariable logistic regression analysis for identifying characteristics associated with not having obtained a first COVID-19 vaccine dose in Belgium and for each of its three regions (Flanders, Brussels and Wallonia). RESULTS: During the study period, 10% (536 716/5 342 110) of the Belgian adult population included in our study sample was not vaccinated with a first COVID-19 vaccine dose. A lower COVID-19 vaccine uptake was found among young individuals, men, migrants, single parents, one-person households and disadvantaged socioeconomic groups (with lower levels of income and education, unemployed). Overall, the sociodemographic and socioeconomic disparities were comparable for all regions. CONCLUSIONS: The identification of sociodemographic and socioeconomic disparities in COVID-19 vaccination uptake is critical to develop strategies guaranteeing a more equitable vaccination coverage of the Belgian adult population.

A time series of tobacco use in Belgium based on a critical appraisal of data sources, 1997-2020 - Sarah Nayani; Robby De Pauw; Brecht Devleesschauwer; Leonor Guariguata (European Journal of Public Health, 2023)

Women’s health report for Belgium: addressing the information gap - Aline Scohy; Gaelle Mogin; Leonor Guariguata; Sarah Nayani; Masja Schmidt; Laura Van den Borre; Robby De Pauw; Vanessa Gorasso (European Journal of Public Health, 2023)
Issue In the last years, Belgian policy makers have become increasingly concerned about health problems affecting only women (e.g. endometriosis) or affecting women in different ways than men (e.g. cardiovascular diseases). The current monitoring tools on the health status in Belgium routinely present information disaggregated by sex. Nevertheless, there is a need to go further than a mere comparison of men and women and strive for gender-sensitive health reporting. Description of the problem To address the information gap pertaining to the health of girls and women, a women's health report for Belgium was developed. The goal of this report is to identify and highlight health issues specific to women or affecting them differently and possible knowledge and data gaps. Results The report highlighted several data gaps, e.g. prevalence of endometriosis and polycystic ovary syndrome, and several opportunities to fill them. The process also uncovered available but underused data on women-specific issues, including fertility treatments, abortions, and contraception. Among the main results, an analysis on girls (11-18 years old) showed an alarming difference in health status compared to boys, starting from a young age and increasing throughout adolescence. For example, girls reported experiencing more psychosomatic symptoms more often than boys with the difference increasing with age. Girls reported more often a negative perception of their health (22%) compared to boys (15%) and more often depressive symptoms (47%) than boys (31%). Conversely, boys were twice as likely to meet WHO recommendations on physical activity. Lessons This first report on women's health in Belgium highlighted the need to collect better information on women-specific issues and the need to promote the use of existing data. Results showed that gender differences in health emerge and increase during adolescence. We strived to put results into context to produce knowledge and recommendations for policymakers. Key messages • Developing a women’s health report allowed to highlight data gaps and underuse of existing data. • Specific interventions should target teenage girls.
Keywords: inequalities; Women' s Health

Belgian national burden of disease study. Guidelines for the calculation of DALYs in Belgium - Robby De Pauw; Vanessa Gorasso; Brecht Devleesschauwer (Sciensano, 2022)
Keywords: BeBOD; burden of disease; Disability-Adjusted Life Years

Burden of disease of COVID-19: Strengthening the collaboration for national studies - Sara Monteiro Pires; Grant M. A. Wyper; Annelene Wengler; José L. Peñalvo; Romana Haneef; Declan Moran; Sarah Cuschieri; Hernan G. Redondo; Robby De Pauw; Scott A. McDonald; Lynelle Moon; Jad Shedrawy; et al. (Frontiers in Public Health, 2022)
Objectives: Quantifying the combined impact of morbidity and mortality is a key enabler to assessing the impact of COVID-19 across countries and within countries relative to other diseases, regions, or demographics. Differences in methods, data sources, and definitions of mortality due to COVID-19 may hamper comparisons. We describe efforts to support countries in estimating the national-level burden of COVID-19 using disability-adjusted life years. Methods: The European Burden of Disease Network developed a consensus methodology, as well as a range of capacity-building activities to support burden of COVID-19 studies. These activities have supported 11 national studies so far, with study periods between January 2020 and December 2021. Results: National studies dealt with various data gaps and different assumptions were made to face knowledge gaps. Still, they delivered broadly comparable results that allow for interpretation of consistencies, as well as differences in the quantified direct health impact of the pandemic. Discussion: Harmonized efforts and methodologies have allowed for comparable estimates and communication of results. Future studies should evaluate the impact of interventions, and unravel the indirect health impact of the COVID-19 crisis.
Keywords: capacity building; Coronavirus; COVID-19; DALY; Disability-adjusted life year; European burden of disease network

COVIMPACT studie - COVID-19 infectie en de lichamelijke, geestelijke en sociale gevolgen op lange termijn : resultaten van 3 en 6 maanden opvolging na infectie - Pierre Smith; Rana Charafeddine; Sabine Drieskens; Robby De Pauw; Karin De Ridder; Stefaan Demarest; Dieter Van Cauteren (2022)

Etude COVIMPACT - Infection COVID-19 et ses implications physiques, mentales et sociales à long terme : résultats du suivi à 3 et 6 mois suivant l’infection - Pierre Smith; Rana Charafeddine; Sabine Drieskens; Robby De Pauw; Karin De Ridder; Stefaan Demarest; Dieter Van Cauteren (2022)

Health Status Report 2021- De gezondheidstoestand in België - Françoise Renard; Aline Scohy; Robby De Pauw; Jure Jurcevic; Brecht Devleesschauwer (Sciensano, 2022)
Keywords: Health monitoring; Health status

Health Status Report 2021 - L'état de santé en Belgique - Françoise Renard; Aline Scohy; Robby De Pauw; Jure Jurcevic; Brecht Devleesschauwer (Sciensano, 2022)
Keywords: Health monitoring; Health status

Health Status Report 2021 - The state of health in Belgium - Françoise Renard; Aline Scohy; Robby De Pauw; Jure Jurcevic; Brecht Devleesschauwer (Sciensano, 2022)
Keywords: Health monitoring; Health status

The non-fatal burden of cancer in Belgium, 2004–2019: a nationwide registry-based study - Vanessa Gorasso; Geert Silversmit; M. Arbyn; Astrid Cornez; Robby De Pauw; Delphine De Smedt; Ian Grant; Grant M. A. Wyper; Brecht Devleesschauwer; Niko Speybroeck (BMC Cancer, 2022)
Background The importance of assessing and monitoring the health status of a population has grown in the last decades. Consistent and high quality data on the morbidity and mortality impact of a disease represent the key element for this assessment. Being increasingly used in global and national burden of diseases (BoD) studies, the Disability-Adjusted Life Year (DALY) is an indicator that combines healthy life years lost due to living with disease (Years Lived with Disability; YLD) and due to dying prematurely (Years of Life Lost; YLL). As a step towards a comprehensive national burden of disease study, this study aims to estimate the non-fatal burden of cancer in Belgium using national data. Methods We estimated the Belgian cancer burden from 2004 to 2019 in terms of YLD, using national population-based cancer registry data and international disease models. We developed a microsimulation model to translate incidence- into prevalence-based estimates, and used expert elicitation to integrate the long-term impact of increased disability due to surgical treatment. Results The age-standardized non-fatal burden of cancer increased from 2004 to 2019 by 6 and 3% respectively for incidence- and prevalence-based YLDs. In 2019, in Belgium, breast cancer had the highest morbidity impact among women, followed by colorectal and non-melanoma skin cancer. Among men, prostate cancer had the highest morbidity impact, followed by colorectal and non-melanoma skin cancer. Between 2004 and 2019, non-melanoma skin cancer significantly increased for both sexes in terms of age-standardized incidence-based YLD per 100,000, from 49 to 111 for men and from 15 to 44 for women. Important decreases were seen for colorectal cancer for both sexes in terms of age-standardized incidence-based YLD per 100,000, from 105 to 84 for men and from 66 to 58 for women. Conclusions Breast and prostate cancers represent the greatest proportion of cancer morbidity, while for both sexes the morbidity burden of skin cancer has shown an important increase from 2004 onwards. Integrating the current study in the Belgian national burden of disease study will allow monitoring of the burden of cancer over time, highlighting new trends and assessing the impact of public health policies.
Keywords: burden of disease; Cancer epidemiology; Disability-Adjusted Life Years; Years lived with disability

Past, present, and future trends of overweight and obesity in Belgium using Bayesian age-period-cohort models - Robby De Pauw; Manu Claessens; Vanessa Gorasso; Sabine Drieskens; Christel Faes; Brecht Devleesschauwer (BMC Public Health, 2022)
Background. Overweight and obesity are one of the most significant risk factors of the twenty-first century related to an increased risk in the occurrence of non-communicable diseases and associated increased healthcare costs. To estimate the future impact of overweight, the current study aimed to project the prevalence of overweight and obesity to the year 2030 in Belgium using a Bayesian age-period-cohort (APC) model, supporting policy planning. Methods. Height and weight of 58,369 adults aged 18+ years, collected in six consecutive cross-sectional health interview surveys between 1997 and 2018, were evaluated. Criteria used for overweight and obesity were defined as body mass index (BMI) ≥ 25, and BMI ≥ 30. Past trends and projections were estimated with a Bayesian hierarchical APC model. Results. The prevalence of overweight and obesity has increased between 1997 and 2018 in both men and women, whereby the highest prevalence was observed in the middle-aged group. It is likely that a further increase in the prevalence of obesity will be seen by 2030 with a probability of 84.1% for an increase in cases among men and 56.0% for an increase in cases among women. For overweight, it is likely to see an increase in cases in women (57.4%), while a steady state in cases among men is likely. A prevalence of 52.3% [21.2%; 83.2%] for overweight, and 27.6% [9.9%; 57.4%] for obesity will likely be achieved in 2030 among men. Among women, a prevalence of 49,1% [7,3%; 90,9%] for overweight, and 17,2% [2,5%; 61,8%] for obesity is most likely. Conclusions. Our projections show that the WHO target to halt obesity by 2025 will most likely not be achieved. There is an urgent necessity for policy makers to implement effective prevent policies and other strategies in people who are at risk for developing overweight and/or obesity.
Keywords: epidemiology; Integrated nested Laplace approximation (INLA); Obesity epidemic; projections; public health

Post COVID-19 condition and its physical, mental and social implications: protocol of a 2-year longitudinal cohort study in the Belgian adult population. - Pierre Smith; Kristiaan Proesmans; Dieter Van Cauteren; Stefaan Demarest; Sabine Drieskens; Robby De Pauw; Laura Cornelissen; Karin De Ridder; Rana Charafeddine (Arch Public Health, 2022)
BACKGROUND: Since the onset of the COVID-19 pandemic, most research has focused on the pathophysiology and management of the acute symptoms of COVID-19, yet some people tend to experience symptoms beyond the acute phase of infection, that is, Post COVID-19 condition (PCC). However, evidence on the long-term health impacts of a COVID-19 infection are still scarce. The purpose of this paper is to describe the COVIMPACT study, which aims to set up a cohort of people who have been tested positive for COVID-19 and study the evolution of their physical, mental and social health over the medium (3 months) and long term (two years), and the factors associated with an (un)favorable evolution. METHODS: COVIMPACT is a longitudinal cohort study organised over a two-years period between April 2021 and April 2023. The eligible population is all people aged 18 years and older, living in Belgium, with a recent COVID-19 infection and contacted by the health authorities for contact tracing. Two questionnaires are used: a baseline questionnaire that aims to assess the initial health status of the participants and their status during the acute phase of the illness, and a follow-up questionnaire that is sent every three months after participants enter into the cohort. A matched non-COVID-19 control group was also selected. As of November 1, 2021, 10,708 people completed the baseline questionnaire (5% of the eligible population) and the follow-up participation rate was 79%. In total, 48% of the cohort participants appeared to fit the proposed case definition of PCC (i.e. report at least one symptom related to their COVID-19 infection three months afterwards). DISCUSSION: This study was designed to provide timely information on the short and long term impact of a COVID-19 infection, to stakeholders such as policymakers, health practitioners and people with PCC. Although the follow-up participation rate was good (79%), the participation rate of the eligible population was low (5%). Compared to other studies, this study has a large sample, of non-hospitalised and hospitalised people, who will be followed over a long period of 3 months to two years post infection, and with a global approach to their health.

Post COVID-19 condition and its physical, mental and social implications: protocol of a 2-year longitudinal cohort study in the Belgian adult population - Pierre Smith; Kristiaan Proesmans; Dieter Van Cauteren; Stefaan Demarest; Sabine Drieskens; Robby De Pauw; Laura Cornelissen; Karin De Ridder; Rana Charafeddine (Archives of Public Health, 2022)
Background: Since the onset of the COVID-19 pandemic, most research has focused on the pathophysiology and management of the acute symptoms of COVID-19, yet some people tend to experience symptoms beyond the acute phase of infection, that is, Post COVID-19 condition (PCC). However, evidence on the long-term health impacts of a COVID-19 infection are still scarce. The purpose of this paper is to describe the COVIMPACT study, which aims to set up a cohort of people who have been tested positive for COVID-19 and study the evolution of their physical, mental and social health over the medium (3 months) and long term (two years), and the factors associated with an (un) favorable evolution. Methods: COVIMPACT is a longitudinal cohort study organised over a two-years period between April 2021 and April 2023. The eligible population is all people aged 18 years and older, living in Belgium, with a recent COVID-19 infection and contacted by the health authorities for contact tracing. Two questionnaires are used: a baseline questionnaire that aims to assess the initial health status of the participants and their status during the acute phase of the illness, and a follow-up questionnaire that is sent every three months after participants enter into the cohort. A matched non-COVID-19 control group was also selected. As of November 1, 2021, 10,708 people completed the baseline questionnaire (5% of the eligible population) and the follow-up participation rate was 79%. In total, 48% of the cohort participants appeared to ft the proposed case defnition of PCC (i.e. report at least one symptom related to their COVID-19 infection three months afterwards). Discussion: This study was designed to provide timely information on the short and long term impact of a COVID19 infection, to stakeholders such as policymakers, health practitioners and people with PCC. Although the follow-up participation rate was good (79%), the participation rate of the eligible population was low (5%). Compared to other studies, this study has a large sample, of non-hospitalised and hospitalised people, who will be followed over a long period of 3 months to two years post infection, and with a global approach to their health.
Keywords: COVID-19; health; longitudinal study; Post COVID-19 condition; Symptoms

The state of health in Belgium, 1990-2019: a benchmarking analysis based on the Global Burden of Disease 2019 study. - Jinane Ghattas; Vanessa Gorasso; Robby De Pauw; Sophie Thunus; Niko Speybroeck; Brecht Devleesschauwer (Arch Public Health, 2022)
BACKGROUND: In a context of decreasing resources and growing health needs, evidence-based health and care policies are essential. This study aims to assess the health trends in Belgium between 1990 and 2019, to compare the Belgian health status to that of the EU-15 countries, and to identify the main drivers in trends over time and country differences within the EU-15. METHODS: We extracted estimates from the GBD 2019 study via the GBD results tool and visualization tools. We compared the Belgian health status with 14 European Union comparator countries between 1990 and 2019, and decomposed the time trends and country differences into the unique contributions of the different underlying causes of death and disability. RESULTS: Life expectancy (LE) in Belgium improved significantly between 1990 and 2019 for both men and women. Belgium age-standardised mortality rates dropped significantly for men (-40%) and women (-33%) between 1990 and 2019. Overall, Belgium age-standardised disability-adjusted life year (DALY) rates dropped by 23%. This decrease is mainly due to decreasing trends in age-standardised years of life lost (YLL) rates while age-standardised years lived with disability (YLD) rates remained stable. Compared to EU-15, Belgium's ranking in terms of age-standardised DALY rates worsened for both men and women in 2019. Self-harm and falls are major causes of disease burden, with DALY rates that are higher than in many other EU-15 countries, indicating a realistic potential for improvement. Lung cancer DALY rates remain worrisome for men, and even show an increasing trend for women. Increasing trends of headache disorders, drug use disorders, and diabetes, require further attention. CONCLUSION: Non-communicable diseases remain the main contributors for health burden in Belgium, with disability accounting for an increasingly larger share of the disease burden. Despite considerable improvements, Belgium's ranking for DALYs decreased between 1990 and 2019 compared to the EU-15. This study identified priority causes of disease burden based on their contributions to current evolutions and EU-15 differences. Since many of these causes are considered to be avoidable, primary and secondary prevention are crucial elements for reducing the burden of disease on the healthcare system.
Keywords: burden of disease; Disability-Adjusted Life Years; Public health monitoring

Years of life lost for 137 causes of death in Belgium by age, sex, and region, 2004-2018 - Aline Scohy; Robby De Pauw; Vanessa Gorasso; Laura Van den Borre; Brecht Devleesschauwer (European Journal of Public Health, 2022)
Keywords: Cause of Death

COVIMPACT Studie: Long COVID en de lichamelijke, psychische en sociale gevolgen – Resultaten van 3 maanden opvolging - Pierre Smith; Rana Charafeddine; Sabine Drieskens; Robby De Pauw; Karin De Ridder; Stefaan Demarest; Dieter Van Cauteren (2021)
Keywords: COVID-19; Langdurige COVID

Etude COVIMPACT : COVID long et ses implications physiques, mentales et sociales – Résultats du suivi à 3 mois - Pierre Smith; Rana Charafeddine; Sabine Drieskens; Robby De Pauw; Karin De Ridder; Stefaan Demarest; Dieter Van Cauteren (2021)
Keywords: COVID-19; long COVID; santé mentale; santé physique

Organizational characteristics: Effect on outcome of ICU COVID-19 patients in Belgium - Authors' reply. - Fabio Silvio Taccone; Nina Van Goethem; Robby De Pauw; Dominique Van Beckhoven; Meyfroidt,G.; Koen Blot (Lancet Reg Health Eur, 2021)

Performance of five rapid serological tests in mild-diseased subjects using finger prick blood for exposure assessment to SARS-CoV-2. - David Triest; Laurence Geebelen; Robby De Pauw; Stéphane De Craeye; Alexandra Vodolazkaia; Mathieu Verbrugghe; Koen Magerman; Lara-Lauren Robben; Pieter Pannus; Kristof Neven; Dirk Ramaekers; Steven Van Gucht; et al. (J Clin Virol, 2021)
OBJECTIVES: Assess the performance of five SARS-CoV-2 rapid serological tests (RST) using finger prick (FP) blood on-site to evaluate their usability for exposure assessment in population-based seroprevalence studies. STUDY DESIGN: Since cross-reactivity with common cold human coronaviruses occurs, serological testing includes a risk of false-positive results. Therefore, the selected cohort for RST-validation was based on combined immunoassay (presence of specific antibodies) and RT-qPCR (presence of SARS-CoV-2) data. RST-performance for FP blood and serum was assessed by performing each RST in two groups, namely SARSCoV- 2 positive (n=108) and negative healthcare workers (n=89). Differences in accuracy and positive and negative predictive values (PPV, NPV) were calculated for a range (1-50%) of SARS-CoV-2 prevalence estimates. RESULTS: The OrientGene showed overall acceptable performance, with sensitivities of 94.4% and 100%, and specificities of 96.6% and 94.4%, using FP blood and serum, respectively. Although three RST reach optimal specificities (100%), the OrientGene clearly outperforms in sensitivity. At a SARS-CoV-2 prevalence rate of 40%, this RST outperforms the other tests in NPV (96.3%) and reaches comparable PPV (94.9%). Although the specificity of the Covid-Presto is excellent when using FP blood or serum (100% and 97.8%, respectively), its sensitivity decreases when using FP blood (76.9%) compared to serum (98.1%). CONCLUSIONS: Performances of the evaluated RST differ largely. Only one out of five RST (OrientGene) had acceptable sensitivity and specificity using FP blood. Therefore, the latter could be used for seroprevalence studies in a high-prevalence situation. The OrientGene, which measures anti-RBD antibodies, can be valuable after vaccination as well.
Keywords: Antibodies, Viral; COVID-19; Humans; SARS-CoV-2; Sensitivity and Specificity; Seroepidemiologic Studies; Serologic Tests

The role of organizational characteristics on the outcome of COVID-19 patients admitted to the ICU in Belgium - Fabio Silvio Taccone; Nina Van Goethem; Robby De Pauw; Xavier Wittebole; Koen Blot; Herman Van Oyen; Tinne Lernout; Marion Montourcy; Geert Meyfroidt; Dominique Van Beckhoven (The Lancet Regional Health - Europe, 2021)

Evaluating the health and health economic impact of the COVID-19 pandemic on delayed cancer care in Belgium: A Markov model study protocol - Yasmine Khan; Nick Verhaeghe; Robby De Pauw; Brecht Devleesschauwer; Gadeyne, Sylvie; Vanessa Gorasso; Yolande Lievens; Niko Speybroeck; Nancy Van Damme; Miet Vandemaele; Laura Van den Borre; Sophie Vandepitte; et al.